Clinical supervision and well-being at work : a four-year follow-up study on female hospital nurses - Koivu, Aija (Publications of the University of Eastern Finland, 2013)
Työnohjaus ja työhyvinvointi : sairaalan naishoitajiin kohdistuva neljän vuoden seurantatutkimus.
Keywords: Burnout, Professional : prevention & control; Comparative Effectiveness Research; Female; Finland; Follow-Up Studies; Hospitals, University; Job Satisfaction; Nurses : psychology; Nursing Staff, Hospital : psychology; Nursing, Supervisory; Occupational Health; Statistics, Nonparametric; Workplace : psychology; hoitohenkilöstö; naiset; osaaminen; työmotivaatio; työnohjaus; vaikuttavuus; työhyvinvointi; hoitotyö; yliopistosairaalat; seurantatutkimus; vårdpersonal; uppföljande undersökning; kunnande; arbetsmotivation; välbefinnande i arbetet; arbetshandledning; universitetssjukhus